A methodology for predicting the color trend to get a three‐colored combination. Issue 1 (29th February 2016) - Hsiao, Shih‐Wen; Yang, Meng‐Hua
Abstract: A color design/selection system for predicting the color trend based on aesthetic measures is proposed in this article. In this method, the analytic hierarchy process theory was used to evaluate the weights for four major consumption style factors in human environment, including Economy, Education, Culture, and Technology. Then 10 product imageries were selected by using the questionnaire, and mapped the images and the factors with the weighted results and clustered both variables with the corresponding ranks. During the implementation procedure, 111 colors samples covering the entire domain of the PCCS (Practical Color Co‐ordinate System) color system were taken, and the aesthetic measure for three‐colored harmony based on aesthetic measure theory was calculated. Then 200 tri‐colored combinations were divided into 10 clusters by using fuzzy clustering. The three‐colored products were then mapped into each cluster with the calculated grand average and Standard Deviation of the imagery values obtained for the three‐colored products. According to the above implementation logic, the relationship among the consumption style factors, the images, as well as the tri‐colored cars can be obtained, and then used to construct a color trend based on market requirement. With the aid of this system, one can get a three‐colored car to match his/her requirement. Although the selection of three‐colored car is taken as an example to specify the methodology, it can also be used to develop a system for other products. © 2016 Wiley Periodicals, Inc. Col Res Appl, 42, 102–114, 2017